2018
DOI: 10.1002/aocs.12089
|View full text |Cite
|
Sign up to set email alerts
|

Thioether‐Functionalized Corn Oil Biosorbents for the Removal of Mercury and Silver Ions from Aqueous Solutions

Abstract: Heavy-metal contamination is one of the most important environmental problems faced in the world, particularly in developing countries. Metals such as silver and mercury from drinking water, food, and air sources can accumulate in living organisms and present significant health concerns. Meanwhile, the demand for these metals in many industries continues to increase. In the present study, thioether-functionalized corn oil (TFCO) from a photoinitiated thiol-ene synthesis was utilized to remove Ag + and Hg 2+ io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Murray et al [23] patented the extractive sequestration of heavy metals from heavy metal-contaminated solid, liquid or gaseous materials, by treating such matter with thiolfunctionalized fatty acids or thiol-functionalized lipids. Since the discovery, only sulphur-modified canola and corn oils have been tried [23,24,27]. Based on our recent comparative study of sorption potentials of thiolated oils with different levels of fatty acid unsaturation, derived from Elaeis guineensis and Glycine max, high level of unsaturation was found desirable [28], and studies have shown CMO to be of high iodine and peroxide values [20], suggesting good candidacy of thiolated CMO as heavy metal sink in wastewater treatment application.…”
Section: Further Background To the Studymentioning
confidence: 99%
“…Murray et al [23] patented the extractive sequestration of heavy metals from heavy metal-contaminated solid, liquid or gaseous materials, by treating such matter with thiolfunctionalized fatty acids or thiol-functionalized lipids. Since the discovery, only sulphur-modified canola and corn oils have been tried [23,24,27]. Based on our recent comparative study of sorption potentials of thiolated oils with different levels of fatty acid unsaturation, derived from Elaeis guineensis and Glycine max, high level of unsaturation was found desirable [28], and studies have shown CMO to be of high iodine and peroxide values [20], suggesting good candidacy of thiolated CMO as heavy metal sink in wastewater treatment application.…”
Section: Further Background To the Studymentioning
confidence: 99%
“…By introducing a minute pre-vortexmixing stage, Murray et al [16] achieved faster equilibration (within 3 hours), using 0.3 g, each of TF-corn oil and TF-canola oil in 3 mL of 600 ppm Ag contaminated water. However, in another study [20], even with pre-vortex-mixing, equilibrium in Ag concentration could not be reached in less than 6 hours, with the co-existence of Hg ions. On the other hand, for liquid-solid adsorption, typical equilibrium contact time ranges from 0.25 to 2.5 hours [22,31].…”
Section: Resultsmentioning
confidence: 86%
“…Since we can barely quit using Ag, remediation strategies are therefore necessary. Besides, the few available works [16,20] on heavy metal remediation by extraction using TF-VOs employed Ag; we also employ Ag in order to have a basis for result comparison.…”
Section: Vegetable Oil + Alkanethiol → Thiolated Oilmentioning
confidence: 99%
See 2 more Smart Citations